RELEVANSI SISTEM PENDIDIKAN PESANTREN TRADISIONAL DALAM ERA MODERNISASI - Eti Fatiroh,; Sukhoiri, Sukhoiri (Journal of Innovation Research and Knowledge, 2023)
Change and development of the Islamic boarding school education system which is increasingly open to patterns from the outside, to respond to the demands of the times, which at this time is more often referred to by some people as the modern era or the era of globalization, where the challenges are getting tougher and the competition is getting tougher in all things, especially in science. To address this, of course, it is necessary to have an effort to balance knowledge and faith in each ummah, which is caused by modernization. The results of the research that has been carried out are: Islamic Boarding School Raudhotul Qur'an Al-Mubarok is still needed because it is able to provide fulfillment of needs in the spiritual and spiritual fields as human eternal needs. In the current era of modernization, where the negative impact of scientific and technological advances (IPTEK) is more felt by society, especially with the emergence of various forms of human moral decadence, the Raudhotul Qur'an Al-Mubarok Islamic Boarding School is still relevant to be maintained. . Advances in science and technology have caused humans to lose peace and mental-spiritual happiness due to competition in the material field, the strong domination of Western culture, human nature that is materialistic and individualistic, and human desires that are only concerned with aspects of worldly life and forgetting the afterlife.